Analisis Potensi Ekonomi Peternakan Kambing Perah Terintegrasi: Studi Kasus: Okane Mochi Farm, Desa Ngaglik - H. Ngatoillah Linnaja; Khozin Gilang Ramadhan; Rizki Agung Khaidar R.; Ahmad Anas; Farah Aliya Zahraa; Vicka Tri Utami; Fasalina Annadiva; Uchi Dista Rahmawati; Ilham Binar Lazuardi; Achmad Manarul Hidayat; Anggit Amelina; Aliya Nabilah; Riska Meilana; Abiyan Maulana; Khusnul Fatimah; Inayatul Husna (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Dairy goat farming holds significant economic potential as a rural enterprise alternative, driven by increasing market demand for goat milk, which is known for being low-allergen and highly nutritious. This article presents a case study on Okane Mochi Farm, a dairy goat farming unit located in Ngaglik Village, Gebang District, Purworejo Regency. This study aims to analyze the breeding management strategies, product innovation, and economic impacts generated by the farm. The method used is field observation and descriptive study of the farm's operations. Observations indicate that the success of Okane Mochi Farm is driven by three main factors: (1) Innovation in selecting superior breeds such as Anglo Nubian and Sapera for high milk productivity; (2) Implementation of strict housing management and hygiene standards to maintain milk quality; and (3) Product diversification through flavored pasteurized milk processing and the utilization of livestock waste into organic fertilizer (zero waste). The study concludes that the upstream-downstream integration model applied by Okane Mochi Farm can serve as a reference for sustainable rural economic empowerment models.